PENGARUH KEPEMIMPINAN TERHADAP KOMITMEN ORGANISASI MELALUI KEADILAN ORGANISASI DAN KEPUASAN KERJA PARA GURU SEKOLAH MENENGAH ATAS NEGERI DAN SWASTA DI JAKARTA - Trisno Prabowo (Media Riset Bisnis & Manajemen, 2005)
The objective of this research is to observe the relations of the LMX leadership model towards the organizational commitment, mediating by the organizational justice and job satisfaction.This research was used survey method, and the respondents are 100 school teachers from public and private high school in Jakarta, selected purposively. The measurement device of the research variable are: LMX leadership measured by the relationship quality, and organizational justice refers to Adam J stacy (1965), Job satisfaction measured using Minnesota Questionnaire and Organizational Commitment measured using Mowday 15 items instruments. All items measured using 5 points likert scale, Using Structural Equation Models was used to test the hypothesis support by Amos 4.01.This research found there is positive relationship between : Leadership towards Organizational Justice, Organizational Justice towards Job Satisfáction, COrganizational Justice towards Organizational Commitment, Job Satisfaction towards Orgnizational Commitment and statistically observe that there is no significant relationship Leadership towards Organizational Commitment.From this reality, showed that in LMX, leadership does not directly promote the organizational Commitment, Organizational Justice and Job Satisfaction should be created first, which are perceived as the outcomes of LMX .Therefore, Organizational Justice and Job Satisfaction existed as the intervening variable.Implications. To whom used LMX model in leadership, the leader have to create Job Satisfaction and Organizational Justice to show Organizational Commitment to his employe. Advisable to make some research to whom uşed ,Transformational model by respondent an employee who works in business field. From that research are Job Satisfaction and Organizational Justice in organization was still intervening variable.